Chemical Constituents of Plants from the Genus Forsythia - Zhang, Qing; Jia, Chenhong; Xu, Haiyun; Wang, Yufang; Zhang, Manli; Huo, Changhong; Shi, Qingwen; Yu, Shuhong (Mini-Reviews in Organic Chemistry, 2012)
The genus of Forsythia (Oleaceae), composing ca. 10˜15 species, is mostly native to eastern Asia and used in oriental traditional medicines. Phytochemical investigations on Forsythia species have shown that triterpenoids, lignans, flavonoids, phenylethanoid glycosides and C6-C2 natural alcohols, accumulated mainly in the fruits, are the major components. Many studies have elucidated that phenolic compounds, including lignans, phenylethanoid glycosides and flavonoids are responsible for the various biological activities of the herbal medicine. This review lists 141 chemical constituents as well as their biosynthetic pathway, bioactivities and quality control as reported until September, 2011 (104 references).
Keywords: Forsythia viridissima